Licensing Revisited: Open Access Clauses in Practice - Schmidt, Birgit; Shearer, Kathleen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
Open access increases the visibility and use of research outputs and promises to maximize the return on our public investment in research. However, only a minority of researchers will "spontaneously" deposit their articles into an open access repository. Even with the growing number of institutional and funding agency mandates requiring the deposit of papers into the university repository, deposit rates have remained stubbornly low. As a result, the responsibility for populating repositories often falls onto the shoulders of library staff and/or repository managers. Populating repositories in this way – which involves obtaining the articles, checking the rights, and depositing articles into the repository – is time consuming and resource intensive work. The Confederation of Open Access Repositories (COAR), a global association of repository initiatives and networks, is promoting a new strategy for addressing some of the barriers to populating repositories, involving the use of open access archiving clauses in publisher licenses. These types of clauses are being considered by consortia and licensing agencies around the world as a way of ensuring that all the papers published by a given publisher are cleared for deposit into the institutional repository. This paper presents some use cases of open access archiving clauses, discusses the major barriers to implementing archiving language into licenses, and describes some strategies that organizations can adopt in order to include such clauses into publisher licenses.